2017
DOI: 10.1111/jcmm.13266
|View full text |Cite
|
Sign up to set email alerts
|

Reduced dosing and liability in methadone maintenance treatment by targeting oestrogen signal for morphine addiction

Abstract: Methadone maintenance treatment (MMT) is the major tapering therapy for morphine addictive patients. There have gender differences reported in response to MMT. This study discovered that the estrogen‐response element single nucleotide polymorphism (ERE‐SNP; rs16974799, C/T) of cytochrome 2B6 gene (cyp2b6; methadone catabolic enzyme) responded differently to MMT dosing. Oestradiol was associated with high MMT dosing, high enantiomer (R‐ or S‐) of 2‐ethylidene‐1,5‐dimethyl‐3,3‐dipheny‐pyrrolidine (EDDP; methadon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 55 publications
0
18
0
1
Order By: Relevance
“…Furthermore, endogenous gonadal hormones impact opioid effects. For example, estrogens can diminish opioids' antinociceptive effects [132], there is evidence of interactions and crosstalk between opioid and estrogen receptors [133], and estrogens may impact the antinociceptive and rewarding effects of methadone through effects on methadone metabolism [134]. In addition, recent preclinical work suggests sex-specific effects of acute opioid withdrawal and subsequent opioid replacement (with methadone or buprenorphine) on regional brain metabolism within regions including the anterior cingulate, amygdala and striatum [135,136].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, endogenous gonadal hormones impact opioid effects. For example, estrogens can diminish opioids' antinociceptive effects [132], there is evidence of interactions and crosstalk between opioid and estrogen receptors [133], and estrogens may impact the antinociceptive and rewarding effects of methadone through effects on methadone metabolism [134]. In addition, recent preclinical work suggests sex-specific effects of acute opioid withdrawal and subsequent opioid replacement (with methadone or buprenorphine) on regional brain metabolism within regions including the anterior cingulate, amygdala and striatum [135,136].…”
Section: Discussionmentioning
confidence: 99%
“…An additional multi-site trial in Canada (N=231) reported that men receiving MMT had lower levels of testosterone than healthy non-MMT males, and that testosterone levels were negatively correlated with methadone dose; there were no significant findings regarding testosterone levels in females in this study 31 . A study in Taiwan (N=411) found that higher methadone doses in women was positively correlated with higher levels of estradiol 32 . Finally, a retrospective chart review of medical records from a publicly-funded treatment center (N=465) reported that women experienced more total adverse events, and specifically headaches, than men following treatment with the opioid antagonist/relapse prevention medication extended-release naltrexone 33 .…”
Section: Sex-based Differences During Treatmentmentioning
confidence: 99%
“…The protocol for detecting mRNA expression followed that detailed in a previous publication (Chiang et al 2017) with some modifications. Total RNA was isolated from the tissue using the Trizol™ reagent (Invitrogen) according to the manufacturer's protocol.…”
Section: Real-time Rt-pcr and Primersmentioning
confidence: 99%